CULTURAL DUE DILIGENCE IN M&A. IMPORTANCE OF SOFT RISKS FACTORS - Warter, Iulian; Warter, Liviu (Annals of Spiru Haret University. Economic Series, 2017)
During the last decades, the corporate world has witnessed a significant rise in the number of cross border mergers and acquisitions (M&As). In cross border M&As, not only different corporate cultures collide, but also different professional and national cultures. The purpose of Cultural Due Diligence (CDD) is to get a coherent image of the intercultural challenges of the M&A in order to be aware of the intercultural risks and opportunities. This article aims to reveal the perception of managers involved in the pre-M&A stage on the soft risks factors that need to be investigated during CDD. This study proposes an appraisal of the most important intercultural issues that need to be considered in M&A. Our contribution to the intercultural aspects of M&A literature consists in improving the current understanding of Cultural Due Diligence content.